Synthesis of 3-ethyl-7,11-Dimethyl-4-Oxa-6, 10-Dodecadienoic Acid By a New Route - Limaye, P.A.; Ghate, S.M. (Asian Journal of Chemistry, 2010)
The derivatives of 3-ethyl-7 ,11-dimethyl-4-oxa-6,10-dodecadienoic acid have enhanced J H activity (100%) against the nymphs of Dysdercus Koenigii. This acid has now been synthesised starting from levulinic acid.